Integrating policy, data and technology in pursuing effective management of ecosystem services - Soares de Moura, Maíse; Cordeiro da Silva, Victor; Ferreira Menezes, Alexandre; Pacheco, Fernando Antonio Leal [UNESP]; Filipe Sanches Fernandes, Luís [UNESP]; Cristina Tarlé Pissarra, Teresa [UNESP]; Monteiro da Costa, Adriana [UNESP] (Elsevier, 2024)
With the growing concerns about the protection of ecosystem functions and services, governments have developed public policies and organizations have produced an awesome volume of digital data freely available through their websites. On the other hand, advances in data acquisition through remote sensed sources and processing through geographic information systems (GIS) and statistical tools, allowed an unprecedent capacity to manage ecosystems efficiently. However, the real-world scenario in that regard remains paradoxically challenging. The reasons can be many and diverse, but a strong candidate relates with the limited engagement among the interest parties that hampers bringing all these assets into action. The aim of the study is to demonstrate that management of ecosystem services can be significantly improved by integrating existing environmental policies with environmental big data and low-cost GIS and data processing tools. Using the Upper Rio das Velhas hydrographic basin located in the state of Minas Gerais (Brazil) as example, the study demonstrated how Principal Components Analysis based on a diversity of environmental variables assembled sub-basins into urban, agriculture, mining and heterogeneous profiles, directing management of ecosystem services to the most appropriate officially established conservation plans. The use of GIS tools, on the other hand, allowed narrowing the implementation of each plan to specific sub-basins. This optimized allocation of preferential management plans to priority areas was discussed for a number of conservation plans. A paradigmatic example was the so-called Conservation Use Potential (CUP) devoted to the protection of aquifer recharge (provision service) and control of water erosion (regulation service), as well as to the allocation of uses as function of soil capability (support service). In all cases, the efficiency gains in readiness for plans’ implementation and economy of resources were prognosed as noteworthy.
Keywords: Data processing; Digital information; Ecosystems; Environmental management; Public policy; Rio das velhas hydrographic basin